Occupational skin diseases in veterinarians: A scoping review - Andeulazia MURDOCK; Rahib K ISLAM; Elizabeth McKEE; Karen GRUSZYNSKI; Robert T. BRODELL; John DASCANIO; Thy N. HUYNH; Vinayak K. NAHAR (GIornale Italiano di Psicologia e Medicina del Lavoro, 2025)
Introduction: Veterinarians are essential to animal health and welfare but are frequently exposed to occupational hazards, including a wide range of skin diseases. These conditions, both infectious and non-infectious, can significantly impact their health and work performance. Methods: This scoping review was conducted according to PRISMA-ScR guidelines to map the existing literature on occupational skin diseases in veterinary professionals. A comprehensive search of four major databases (PubMed, Scopus, Web of Science, Google Scholar) was performed to identify studies published between January 2000 and December 2024. Eligible articles addressed the prevalence, etiology, risk factors, clinical features, and preventive strategies related to skin diseases in veterinarians. Results: Thirty one -one studies were included in the final synthesis. The most frequently reported conditions were zoonotic skin infections (e.g., Orf, anthrax, tularemia, MRSA), allergic and irritant contact dermatitis, and injuries due to bites, scratches, or needlestick accidents. Major risk factors included direct contact with animals, inadequate use of personal protective equipment (PPE), and limited occupational safety training. Significant variability in disease prevalence was observed across geographical regions and practice types. Conclusions: Occupational skin diseases remain a substantial yet underrecognized risk for veterinarians. Enhancing training, improving PPE accessibility and compliance, and developing evidence-based infection control policies are key to mitigating these risks. Future research should focus on intervention studies and regulatory harmonization to support safe veterinary practice worldwide.